Rationing Justice by Rationing Lawyers - Peter A. Joy (Washington University Journal of Law & Policy, 2011)
The number of lawyers in the United States continues to increase, but low and middle-income persons still find it difficult, if not impossible, to afford legal assistance. National and state surveys reveal that more than 80 percent of the civil legal needs of the poor go unmet, as do a majority of the needs of middle-income persons. Legal representation can often dramatically increase a person’s ability to win at trial or to negotiate a favorable outcome, and the lack of access to lawyers effectively closes the courthouse doors for millions. This Article focuses on the crisis in Missouri's public defender system due to excessive caseloads and how the rationing of lawyers limits access to justice for the accused. The Article proceeds in four parts: Part I discusses the Sixth Amendment and its importance to the accused; Part II briefly analyzes why the current standard for ineffective assistance of counsel contributes to the problem of excessive caseloads for state public defenders; Part III focuses on the ethical obligations of public defenders facing excessive caseloads; and Part IV outlines what needs to occur in order to improve the justice system for the accused.
Keywords: Legal assistance to the poor; Legal ethics; Public defenders; Right to counsel; United States Constitution; Missouri; United States